Your Wish, My Command – Speeding up Projects in the Transportation Industry Using Ontologies. Issue 1 (July 2017) - Chalé Góngora, Hugo Guillermo; Llorens, Juan; Gallego, Elena
Abstract: This paper presents the results of an exploratory study conducted at ALSTOM on the application of knowledge‐centric approaches to the requirements definition process. The original scope of the study concerned the application of ontologies to analyze and improve the quality of specification documents in an industrial context. An additional idea quickly emerged as a collateral benefit of the study to extend the usage of the gathered knowledge base in order to perform computer‐assisted identification of requirements from structured and unstructured documents. The purpose of this new approach is to improve the execution of projects in railway transportation by accelerating the requirements management and development processes and, in particular, the stakeholder requirements capture and elicitation activities.